El “indio” don Gaspar Jurado y su lucha por la escribanía de cámara de la Real Audiencia de Lima (1811-1812) [Estudios] - Bazán Díaz, Marissa (2015)
This article studies the judicial equality awarded to the indios and mestizos during the Courts of Cádiz, since the judgment of the “indio” Gaspar Jurado, who reclaimed access to the position for Clerk of the Chambers for the Royal Audience for Lima. This allegation caused the objection of the Spanish Clerks based on the relative argument to the confusion about the origins of his birth, associating it with the caste “zambaiga”. Jurado obtained the sentence in his favor since he used the criteria of equality, demonstrating the rapidness with which new dispositions of Cadiz were disseminated and it´s interpretations in the judicial imaginary of the Hispanic empire.